SOCIALIZATION OF COOPERATIVE ACCOUNTING SOFTWARE BMT DMI PEKANBARU CITY - RIO ANDISFA; Annie Mustika Putri (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
Islamic financial institutions or can be called interest-free banks are finance/banking whose operations and products are developed based on the arguments of the Qur'an and the Hadith of the Prophet SAW. Islamic financial institutions are banks whose working mechanism uses a profit-sharing system. Currently IAI (Indonesian Accounting Associations) has issued a statement of financial accounting standards (PSAK) which regulates Islamic Financial Accounting. The purpose of this activity is to provide knowledge and insight to readers about the role of the importance of accounting software in sharia cooperatives in recording their financial statements in the era of all-technology at this time, the role of technology in each activity is greatly assisted, for that it is necessary to have good socialization related to software.Accounting in Sharia cooperatives. And help the Bmt Dmi in Pekanbaru. As for the target, the members/managers of the sharia cooperative Bmt Dmi Pekanbaru City understand and understand Accounting Software which can facilitate managers in recording financial statements properly and correctly. This activity will greatly assist the management of Bmt Dmi to run the program and its financial system. The result is that Accounting Software can help Bmt Dmi in doing accounting